Adopting Hybrid Learning: A Case Study of SMP Negeri 1 Pameungpeuk West Java-Indonesia Response to Distance Learning Challenges - Rifa Rizkia Fakhrini; Nora Saiva Jannana (Journal of Islamic Education Management Research, 2023)
Purpose  – This research is motivated by the challenges faced by students and teachers at SMP Negeri 1 Pameungpeuk, Garut, West Java, in conducting effective distance learning during the COVID-19 pandemic. Recognizing the limitations impacting students' understanding and the subsequent learning effectiveness, the government authorized face-to-face learning under specific conditions. This study explores the implementation of hybrid learning at SMP N 1 Pameungpeuk as an alternative to address the constraints faced by students in distance learning. Design/methods/approach  – Conducted as a qualitative descriptive study, this research utilizes purposive sampling to select informants. Data collection methods include observation, interviews, and documentation. Analysis techniques involve transcript analysis, coding, grouping, and comparing and contrasting. Validity is ensured through source triangulation. Findings  – The study reveals that hybrid learning, as implemented by SMP N 1 Pameungpeuk, is an effective solution for students facing constraints in distance learning. The hybrid approach allows teachers to understand students' states, characters, and academic development. Adjustments to the learning plan involve a single-sheet lesson plan, thirty-minute subject sessions using various applications, and evaluation through assigned student tasks. Research implications/limitations  – The research implies the potential of hybrid learning as a viable alternative in challenging circumstances. Rules include the specific context of SMP Negeri 1 Pameungpeuk and the dynamic nature of distance learning constraints during the pandemic. Practical implications  – The findings offer valuable insights for educational institutions considering hybrid learning as an alternative to address challenges in distance learning. Adjusting learning plans and utilizing various applications highlights practical strategies for effective implementation. Originality/value  – This research contributes to the literature by showcasing the implementation of hybrid learning as a response to the limitations of distance learning, particularly during the COVID-19 pandemic. The study's originality lies in its detailed exploration of the practical aspects of hybrid learning, offering valuable insights for educational institutions navigating similar challenges.